Morality in Plutarch's "Life of Cimon" - Giroux, Chandra (Université d'Ottawa / University of Ottawa, 2016)
Understanding Plutarch’s Parallel Lives as a literary text is the focus of current scholarship. However, to this date, no one has looked at Plutarch’s Life of Cimon to analyze what it reveals about morality. My thesis endeavours to understand how Plutarch shapes Cimon as a literary character to bring to light the moral focus of this Life. It first investigates Plutarch’s life and the atmosphere in which he lived to understand what influenced his writing. Chapter One follows with a discussion of the composition of the Lives to understand how they are organized. The insistence on reading each book’s four parts (proem, Life 1, Life 2, synkrisis) to fully appreciate their moral relevance leads to Chapter Two, which dissects the main components of Plutarch’s moral mirror. This provides the necessary background needed for Chapter Three’s case study of Plutarch’s Cimon. Here, I argue that the main moral message contained therein is the importance of generosity and euergetism.
Keywords: Plutarch; Parallel Lives; Morality; Cimon; Euergetism